The Role of Think Talk Write Learning Model Assisted by Wordwall Media on Students’ Critical Thinking Skills - Patimah, Nenden Lu'lu; Sartika, Sri Hardianti; Sadiah, Ati (Cakrawala: Jurnal Pendidikan, 2023)
This study aims to overcome the low level of critical thinking skills among students in the class 11th Social Science at SMAN 10 Tasikmalaya, specifically in Economics. The study used the Think Talk Write (TTW) learning model assisted by Wordwall media as an X variable. The research design is quasi-experimental with a non-equivalent control group. The T-test analysis findings show the following: (1) There is an improvement in critical thinking abilities in the experimental group, with a sig value (2-tailed) of 0.000 0.05. (2) There is also an improvement in critical thinking skills in the control group, with a sig value (2-tailed) of 0.000 0.05. (3) With a sig value (2-tailed) of 0,199 > 0,05, there is no difference in critical thinking skills improvement between the experimental and control groups. As a result, it can be stated that employing the Think Talk Write (TTW) model assisted by Wordwall media has a considerable influence on strengthening students’ critical thinking abilities.